A Low Glycemic Index Staple Diet Reduces Postprandial Glucose Values in Asian Women With Gestational Diabetes Mellitus. (1st December 2014) - Hu, Zhi-Geng; Tan, Rong-Shao; Jin, Di; Li, Wei; Zhou, Xiao-Yan
Abstract : Background: A low glycemic index (GI) diet is beneficial for glucose control in patients with diabetes mellitus. This study aimed to investigate the influence of a low-GI diet on postprandial glucose levels in women with gestational diabetes mellitus (GDM). Methods: Pregnant women with GDM were randomized to receive a normal diabetic control diet or a low-GI staple diet for 5 days. A low-GI staple food was used to replace rice in lunch and dinner for the low-GI staple diet group, whereas the total energy and carbohydrate levels remained equal in both groups. Fasting and postprandial glucose levels were determined daily. Results: A total of 140 pregnant women with GDM were included in the study, including 66 in the low-GI staple diet group and 74 in the normal diabetic diet control group. No differences existed in baseline characteristics between the 2 groups (all P > 0.05). After dietary intervention, glucose levels were significantly reduced in the low-GI staple diet group (all P < 0.01) and the control group (all P < 0.008). Postintervention glucose values after breakfast, lunch, and dinner were significantly reduced in the treatment group compared with those in the control group (all P < 0.05). The percentage changes from baseline of all glucose values were significantly greater in the treatment group than in the control group (all P < 0.05). Conclusions: A low-GI staple diet significantly reduces postprandial glucose levels in women with GDM.